Modification of sago starch by graft copolymerization. Effect of reaction conditions on grafting parameters - Lutfor, M.R.; Sidik, S.; Haron, J.; Rahman, M.Z.A.; Ahmad, M. (Taylor & Francis, 2003)
Graft copolymerization of acrylonitrile onto sago starch was carried out by a free radical initiating process in which the ceric ion (Ce4+) was used as an initiator. The reaction conditions significantly influence the graft copolymerization. The percentage of grafting, grafting efficiency and rate of grafting were all dependent on the concentration of ceric ammonium nitrate (CAN), acrylonitrile (AN), sago starch (AGU, anhydro glucose unit), mineral acid (H2SO4), and the reaction temperature and period. The optimum yield was obtained when the concentrations of CAN, AN, AGU and H 2SO4 were used at 9.61 × 10-3, 0.653, 0.152 and 0.187molL-1, respectively. The optimum temperature and reaction period were 50°C and 90 min, respectively. The rate of graft copolymerization was examined using the experimental results and the reaction mechanism. The polyalcrylonitrile grafted sago starch was characterized by using FT-IR spectroscopy, DSC and SEM analysis.